2015
DOI: 10.1016/j.applanim.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of daily activity and circadian rhythm in the Iberian lynx (Lynx pardinus)

Abstract: 34The aim of this paper is to describe the ontogeny of the circadian activity rhythms in captive-35 born Iberian lynx (Lynx pardinus) from birth to subadult age and to verify if they develop a 36 bimodal circadian pattern similar to the one they show in the wild. The amount of daily activity 37 and the circadian rhythmicity of 61 Iberian lynx (48 mother-raised and 13 hand-reared) cubs 38 were studied in two breeding centers. During the first month of life, the cubs were active 30% of 39 the day. Activity incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…In addition, daily changes in light and animal’s activity partially explained the variation in HR, with higher HR averages observed at dusk and night, when animals were more active. Rearing method affected the daily activity pattern in the present study, as described in other zoo animals ( Berger, 2011 ; Yerga et al , 2015 ), with hand-reared wolves being less ‘nocturnal’ than parent-reared wolves. Yet, this outcome should be confirmed with a larger sample size.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, daily changes in light and animal’s activity partially explained the variation in HR, with higher HR averages observed at dusk and night, when animals were more active. Rearing method affected the daily activity pattern in the present study, as described in other zoo animals ( Berger, 2011 ; Yerga et al , 2015 ), with hand-reared wolves being less ‘nocturnal’ than parent-reared wolves. Yet, this outcome should be confirmed with a larger sample size.…”
Section: Discussionsupporting
confidence: 54%
“…For captive cheetahs, imprinting on humans can cause behavioural problems [ 7 ]. Hand-reared Iberian lynx ( Lynx pardinus ) cubs were found to have more contact time with keepers, and this can increase occurrences of imprinting [ 57 ]. While keepers are also present around parent-reared individuals during daily husbandry routines, past research has found that parent-reared black rhinos ( Diceros bicornis ) and maned wolves ( Chrysocyon brachyurus ) had less affinity for their keepers than hand-reared counterparts [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The daily distribution of locomotor activity has been studied in numerous mammalian species [10][11][12], but few studies have been conducted on felids. A few general studies of activity rhythms have been conducted on felids in the wild [13][14][15] and in captivity [16][17][18], but detailed studies on various species have yet to be accomplished. We describe here a detailed analysis of the daily activity rhythms of the domestic cat and of eight of the ten feral felid species that are indigenous to South America [19], which belong to three different genera (Panthera, Puma, and Leopardus) and have different life styles in terms of active times, social structure, maternal investment, etc.…”
Section: Introductionmentioning
confidence: 99%